THE CORACOIDS IN FUNCTIONAL AND MORPHOLOGICAL STUDIES OF PENGUINS (AVES, SPHENISCIDAE) OF THE EOCENE OF ANTARCTICA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The partial articulated skeleton MLP 77-V-10-1 comes from the upper levels of La Meseta Formation (Seymour Island, Antarctica) at the southwestern slope of the plateau. These remains were found in the Submeseta Allomember, within the Anthropornis nordenskjoeldi Biozone, dated at 34.2 Ma using strontium isotope ratios from shells. MLP 77-V-10-1 is a giant penguin, probably the largest ever described, whose coracoids are strikingly wide at the distal surface. The present contribution is a study of this new fossil penguin, with particular emphasis on the coracoids. The osteography and associated muscles are described. Functional connotations of coracoid morphology are thoroughly discussed and its implications on the mechanics of diving are explored. We concluded that the coracoid morphology suggests a change in diving strategy from the earliest penguins until the living representatives. In the oldest penguins, the improvement of diving capacity would have been linked to the development of stronger bone and probably muscular structures enabling endurance of greater forces operating in a denser medium. In contrast, the Neogene penguins would have optimized the force action of the flight apparatus by developing more precise movements, adjusting the angle of attack of each of the effective forces.
Keywords: Eocene; Antarctica; Fossil Penguins; Functional morphology; Diving mechanics